2010
DOI: 10.4236/abb.2010.11002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of L-ornithine hydrochloride ingestion on human growth hormone secretion after strength training

Abstract: This study aimed to examine the effect of L-ornithine hydrochloride ingestion on serum growth hormone secretion response after strength training in young men who did not regularly engage in high intensity exercise. Ten healthy young males without workout habits (age: 22.2 +/-1.0 yr). Subjects performed biceps curl strength training after L-ornithine hydrochloride and placebo ingestions. They participated in both of the above conditions randomly with a week interval in between. Serum growth hormone and ornithin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…In addition, although many effects of its ingestion have not been clarified, the L-ornithine promotes growth hormone release by stimulating the pituitary gland (Evain-Brion et al, 1982;Demura et al, 2010). Additionally, L-ornithine is one product of arginase enzyme activity on L-arginine, and is also related to the creation of urea.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although many effects of its ingestion have not been clarified, the L-ornithine promotes growth hormone release by stimulating the pituitary gland (Evain-Brion et al, 1982;Demura et al, 2010). Additionally, L-ornithine is one product of arginase enzyme activity on L-arginine, and is also related to the creation of urea.…”
Section: Introductionmentioning
confidence: 99%
“…These results may suggest that the effect of Orn on mTORC1 signaling was not exerted through its metabolite, citrulline. Another mechanism behind the effects of Orn on mTORC1 pathway was thought to be through growth hormone release, because it was reported that Orn has the potential to stimulate growth hormone release (9). Orn administration tended to increase plasma growth hormone levels (P<0.1, Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In pharmacological therapy, Orn is used to decrease blood ammonia levels and reduce the symptoms of hepatic encephalopathy associated with liver cirrhosis (6). In addition, many human studies have indicated several beneficial effects of Orn, including attenuation of fatigue evoked by exercise or alcohol consumption (7,8), stimulation of growth hormone release (9), and improvements in sleep disturbance (10,11). Furthermore, a report indicated that the addition of Orn to a basal diet induced the blood growth hormone level and the rate of protein synthesis in the liver and gastrocnemius muscle (12).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible that there is no significant difference in serum growth hormone concentration between both conditions. However, Demura et al [16] examined the effect of L-ornithine hydrochloride ingestion on enhancement of growth hormone secretion after resistance exercise using 10 male adults and reported that serum growth hormone concentration 30 min after resistance exercise in the L-ornithine hydrochloride ingestion condition was greater than that of the placebo ingestion condition. The inconsistency between the results of the present and previous studies may be attributed to measurement time of growth hormone rather than quantity of L-ornithine hydrochloride ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…Bucci et al [15] examined the effect of L-ornithine hydrochloride ingestion on enhancement of growth hor-mone secretion in body builders and reported that the blood concentration of growth hormone increased with L-ornithine hydrochloride ingestion. Moreover, Demura et al [16] examined the effect of L-ornithine hydrochloride ingestion before resistance exercise on postexercise growth hormone secretion in ten healthy male adults and reported that blood concentration of growth hormone after resistance exercise was greater in the L-ornithine hydrochloride ingestion condition than the placebo ingestion condition. Namely, enhanced growth hormone secretion has been suggested by not only ingestion of free amino acids such as L-ornithine, but also subsequent resistance exercise after amino acid ingestion.…”
Section: Introductionmentioning
confidence: 99%